2015
DOI: 10.1089/thy.2014.0098
|View full text |Cite
|
Sign up to set email alerts
|

Management of Recurrent/Persistent Nodal Disease in Patients with Differentiated Thyroid Cancer: A Critical Review of the Risks and Benefits of Surgical Intervention Versus Active Surveillance

Abstract: Identification of recurrent/persistent disease requires a team decision-making process that includes the patient and physicians as to what, if any, intervention should be performed to best control the disease while minimizing morbidity. Several management principles and variables involved in the decision making for surgery versus active surveillance were developed that should be taken into account when deciding how best to manage a patient with DTC and suspected recurrent or persistent cervical nodal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 121 publications
3
70
0
4
Order By: Relevance
“…Selected cases can be managed expectantly or by means of surgical resection, thermal destruction, or alcohol ablation. 4042 …”
Section: Differentiated Thyroid Carcinomamentioning
confidence: 99%
“…Selected cases can be managed expectantly or by means of surgical resection, thermal destruction, or alcohol ablation. 4042 …”
Section: Differentiated Thyroid Carcinomamentioning
confidence: 99%
“…Tumors with !1-2 cm or low tumor burden, in most cases, should be followed actively without additional therapy (Cooper et al 2009). Several studies suggest that small (!1 cm) metastatic lymph nodes and also thyroid bed nodules can be safely followed for years with ultrasound (Rondeau et al 2011, Guy et al 2014, Urken et al 2014, Tufano et al 2015. Small soft tissue metastasis can also be followed with cross-sectional images.…”
Section: Active Surveillancementioning
confidence: 99%
“…[1][2][3][4] Previous studies have shown that even though differentiated thyroid cancer demonstrates a low mortality rate, long-term recurrence after initial treatment can be common occurring in up to 35% of cases, with lymph nodes being the most frequent site of recurrence. [7][8][9][10] In consideration of these findings, removal of clinically apparent lymph node metastases identified by imaging would be of great importance. [7][8][9][10] In consideration of these findings, removal of clinically apparent lymph node metastases identified by imaging would be of great importance.…”
Section: Introductionmentioning
confidence: 99%